Amino acids in hematologic malignancies: Current status and future perspective - Wang, Mengyao; Zhao, Ailin; Li, Meng; Niu, Ting (Frontiers in Nutrition, 2023)
In recent years, growing emphasis has been placed on amino acids（AAs）and their role in hematologic malignancies. Cancer cell metabolism is altered during tumorigenesis and development to meet expanding energetic and biosynthetic demands. AAs not only act as energy-supplying substances, but also play a vital role via regulating key signaling pathways, modulating epigenetic factors and remodeling tumor microenvironment. Targeting AAs may be an effective therapeutic approach to address the current therapeutic challenges. Here, we provide updated overview mechanisms by which AAs facilitate tumor development and therapy resistance. We also summarize novel therapies targeting AAs, focusing on recent advances in basic research and their potential clinical implications.